Assessing Organizational Culture: An Important Step for Enhancing the Implementation of Junior High School-Based Pesantren - Muhammad Anggung Manumanoso Prasetyo; Khairul Anwar (STAI Hubbulwathan Duri, 2021)
Pesantren is required to be competitive in the field of science. The presence of the SMP-BP program is one of the efforts to improve science education in Islamic boarding schools. Leadership and culture are essential factors in encouraging the level of organisational management effectiveness. This article aims to deepen knowledge of practices in pesantren culture and its dynamics concerning the effectiveness of pesantren organisations (SMP-BP implementation). The research paradigm is qualitative. Data is obtained through interviews and observations. This research involved pesantren managers consisting of leaders, deputy leaders, and several pesantren teachers in Aceh Tenggara district. This research is necessary because it examines a culture in a practical perspective that visualises and concretises the complexities in Islamic boarding school culture concerning the dynamics of work improvement. The results showed that the formation of pesantren culture is a fundamental principle in creating organisational effectiveness. This study investigates the forms of practice carried out by pesantren managers in increasing organisational effectiveness. Identifying the improvement in the management of pesantren is influenced by the policy factors of the pesantren leadership. Three practices identified in an organisational culture approach are leadership mechanisms, management revitalisation, change commitment, and building organisational culture. The research has implications as material for further studies on strengthening organisational culture both contextually and conceptually on the dynamics of education management.